2022
DOI: 10.1177/02676591221096078
|View full text |Cite
|
Sign up to set email alerts
|

Awake extracorporeal life support and physiotherapy in adult patients: A systematic review of the literature

Abstract: Objective The Awake Extracorporeal Life Support (ECLS) practice combined with physiotherapy is increasing. However, available evidence for this approach is limited, with unclear indications on timing, management, and protocols. This review summarizes available literature regarding Awake ECLS and physiotherapy application rates, practices, and outcomes in adults, providing indications for future investigations. Methods Four databases were screened from inception to February 2021, for studies reporting adult Awa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…A recent systematic review on physiotherapy during awake extracorporeal life support (ECLS), including 56% of cases of venovenous ECMO, reported a 63% of success rate in successful extubation during ECLS, which is consistent with our findings (78). Compared with this study, our systematic review focuses on patients with respiratory failure, is more updated, and include data on reasons for failure of awake ECMO and major complications.…”
Section: Discussionsupporting
confidence: 91%
“…A recent systematic review on physiotherapy during awake extracorporeal life support (ECLS), including 56% of cases of venovenous ECMO, reported a 63% of success rate in successful extubation during ECLS, which is consistent with our findings (78). Compared with this study, our systematic review focuses on patients with respiratory failure, is more updated, and include data on reasons for failure of awake ECMO and major complications.…”
Section: Discussionsupporting
confidence: 91%
“…It is now widely accepted that rehabilitation is a standard of care, and researchers may want to explore new directions in this field. Although several studies have shown that mobilization and exercise are possible for patients on ECMO support, 14,15,[23][24][25]27,28,48 their rehabilitative potential is still underestimated at present. 49 On the other hand, implementing early and active rehabilitation is a well-established concept in critically ill patients and ICU settings, although the definition of "early" and the dosage of mobilization remain controversial and uncertain.…”
Section: Covid-19mentioning
confidence: 99%
“…[17][18][19][20][21][22] The first consensus document on physiotherapy for this class of patients was published in 2017, providing evidence-based support for rehabilitation professionals. 23 Since then, various studies have explored rehabilitation methods for patients undergoing ECMO, 14,15,[24][25][26][27] while a recent EuroELSO survey was designed to capture modalities and characteristics of the physiotherapeutic treatments currently provided in international ECMO settings. 28 Rehabilitation of patients on ECMO support involves a complex delivery of assessment procedures and techniques aiming at restoring or maintaining neuromuscular, cognitive and respiratory functions in an acute context of reduced or absent mobility of the person.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The simplest clinical assessment of respiratory drive is to ask the patient. The 11-point modified Borg dyspnoea scale functions similarly to a visual analogue scale 132 and is well validated in conventional ventilation 133,134 and ECMO [135][136][137] The Borg score is also readily repeated allowing changes in native lung and membrane function to be tracked. Most ECMO-supported patients are not able to self-report dyspnoea and so this must be inferred by other means.…”
Section: Monitoring Respiratory Drivementioning
confidence: 99%